2021
DOI: 10.3390/ma14051171
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as a Protective Matrix for the Squaraine Dye

Abstract: Chitosan was used as a protective matrix for the photosensitive dye-squaraine (2,4-bis[4-(dimethylamino)phenyl]cyclobutane-1,3-diol). The physicochemical properties of the obtained systems, both in solution and in a solid-state, were investigated. However, it was found that diluted chitosan solutions with a few percent additions of dye show an intense fluorescence, which is suppressed in the solid-state. This is related to the morphology of the heterogeneous modified chitosan films. The important advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Amongst natural biopolymers, the amino-polysaccharide chitosan shows promising features as the incorporation matrix of bioactive additives, such as plant-derived oils or extracts [ 27 ]. Chitosan has gained attention in this field due to its many unique properties such as good film-forming ability, edibility, biodegradability, biocompatibility, nontoxicity and antimicrobial activity against fungi, Gram-positive bacteria and Gram-negative bacteria [ 20 , 28 , 29 , 30 ]. Moreover, chitosan has the ability to interact through its functional groups with different compounds in plant oils, promoting their entrapment [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amongst natural biopolymers, the amino-polysaccharide chitosan shows promising features as the incorporation matrix of bioactive additives, such as plant-derived oils or extracts [ 27 ]. Chitosan has gained attention in this field due to its many unique properties such as good film-forming ability, edibility, biodegradability, biocompatibility, nontoxicity and antimicrobial activity against fungi, Gram-positive bacteria and Gram-negative bacteria [ 20 , 28 , 29 , 30 ]. Moreover, chitosan has the ability to interact through its functional groups with different compounds in plant oils, promoting their entrapment [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is extremely promising for the development of novel useful materials. 96 The examples presented above confirm the crucial role played by squaraine dyes in many areas of science and technology. Importantly, the application possibilities are not limited to the medical field.…”
Section: Reviewmentioning
confidence: 55%
“…Generally speaking, studies show a photoprotective effect of chitosan, which was also observed in composites of this polysaccharide with squaraine and porphyrazine-type dyes [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%